2011
DOI: 10.1177/1062860610395929
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Variation in Missed Nursing Care

Abstract: Quality of nursing care across hospitals is variable, and this variation can result in poor patient outcomes. One aspect of quality nursing care is the amount of necessary care omitted. This paper reports on the extent and type of nursing care missed and the reasons for missed care. The MISSCARE Survey was administered to nursing staff (n = 4086) who provide direct patient care in ten acute care hospitals. Missed nursing care patterns, as well as reasons for missing care (labor resources, material resources, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
306
7
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(365 citation statements)
references
References 25 publications
42
306
7
10
Order By: Relevance
“…Our results found multiple missed care opportunities in the 24 hours before diagnosis of pneumonia. Numerous previous studies have reported that missed fundamental hospital care is linked to poorer patient outcomes, 17,[19][20][21][22][23][24][25] a finding that is also supported by our data.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results found multiple missed care opportunities in the 24 hours before diagnosis of pneumonia. Numerous previous studies have reported that missed fundamental hospital care is linked to poorer patient outcomes, 17,[19][20][21][22][23][24][25] a finding that is also supported by our data.…”
Section: Discussionsupporting
confidence: 91%
“…The retrospective nature of the study prevents us from identifying the exact reasons for missed fundamental hospital care; however, reasons from other research include labor, material resources, and poor communication. 17,21 Furthermore, the ICD-9-CM codes may underestimate the actual number of NV-HAP cases because a point-prevalence observation was not conducted. Because we required CDC criteria, cases in immunocompromised patients may have been missed if cultures for pneumonia were not obtained, which is often the case.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have revealed several factors that might explain why many patients in this study did not receive any analgesic during the first four hours in the postoperative period. For instance, lack of analgesic availability at the time of patients' need and shortage of nurses are the reasons why patients do not receive the medication on time [12]. Other reasons might include the set routines of analgesic administration in the ward, and patients' attitudes.…”
Section: Type Of Analgesic Atmentioning
confidence: 99%
“…A study by Kalisch and Tschannen et al [12] conducted in an acute care setting in 10 hospitals in the United States found that failure to administer medication on time was among the top five care elements overlooked by nurses. In Malaysian government hospitals generally, only analgesics such as morphine, pethidine, diclofenac, and paracetamol are available in the ward at any time.…”
Section: Type Of Analgesic Atmentioning
confidence: 99%